Determinan Kemiskinan Di Provinsi Daerah Istimewa Yogyakarta Tahun 2012-2019 - Rifki Khoirudin; Muhammad Safar Nasir (Journal of Economic, Bussines and Accounting (COSTING), 2022)
Until now, poverty in Indonesia is still a homework that has not been completely resolved. Thus, it is necessary to analyze the factors in influencing poverty. This study aims to analyze the population, inflation rate, economic growth, and the open unemployment rate on the poverty rate in D.I.Yogyakarta Province in the 2012-2019 time period. The type of secondary data used was obtained from the D.I. Provincial Central Statistics Agency. Yogyakarta, which consists of a cross section in 5 regencies/cities in the Province of D.I. Yogyakarta and time series from 2012-2019. The analytical tool used in estimating the regression model is the Fixed Effect Model (FEM). The results showed that simultaneously all independent variables had a significant effect on the poverty level. Partially, the variables of population and economic growth have a negative and significant effect on the level of poverty in the Province of D.I. Yogyakarta. Meanwhile, the inflation rate and the open unemployment rate have no effect on the poverty level. Keywords: poverty, population, economic growth, fixed effect model